Effects of branched-chain amino acids (BCAAs) on the progression of advanced liver disease: A Korean nationwide, multicenter, retrospective, observational, cohort study. Issue 24 (June 2017) - Park, Jung Gil; Tak, Won Young; Park, Soo Young; Kweon, Young Oh; Jang, Se Young; Lee, Yu Rim; Bae, Si Hyun; Jang, Jae Young; Kim, Do Young; Lee, June Sung; Suk, Ki Tae; Kim, In Hee; et al.
Abstract : Abstract: Evidence of the potential benefits of long-term oral branched-chain amino acid (BCAA) supplementation in reducing the severity of liver disease is limited. Patients who were diagnosed with liver cirrhosis with a Child–Pugh (CP) score of 8–10 were included. The BCAA group consumed BCAAs daily for at least 6 months, and the control group consumed a diet without BCAA. We analyzed the improvements based on the model for end-stage liver disease (MELD) score, CP score, incidence of cirrhosis-related complications, and event-free survival over 2 years. Among the 867 recruited patients, 307 (166 in the BCAA group and 141 in the control group) were analyzed. The BCAA group was divided into 3 subgroups, whose patients consumed 4.15 g, 8.3 g, or 12.45 g of BCAAs daily for the analysis. There were significant differences in the CP score, albumin, and hepatic encephalopathy between the 2 groups at baseline. After matching the propensity scores, we analyzed patients in the BCAA-12.45 g group (12.45 g of BCAAs daily, n = 41) and matched control group (n = 41). The MELD score significantly improved in the BCCA-12.45 g group compared to the matched control group ( P = . 004). The changes in the serum bilirubin level ( P = . 014) and CP score ( P = . 033) over time also differed significantly between the 2 groups. The incidence rates of cirrhosis-related complications ( P = . 973) and development of hepatocellular carcinoma (2 cases each) did not differ significantly between the 2 groups. Long-term oral BCAA supplementation has beneficial effects in patients with advanced liver cirrhosis. A further large-scale prospective study is needed to delineate these beneficial effects. Abstract : Supplemental Digital Content is available in the text